On the Peculiarities of Construction Process Organization in Novgorod of the Pre-Mongol Period - Bulkin, Valentin A.; Antipov, Ilya V. (Actual Problems of Theory and History of Art, 2017)
The reconstruction of the church building process is one of the most important and complicated questions in the study of the history of early Russian architecture.The continuity in the church construction process is common for the architecture of Novgorod and its lands in the 12th century. It is possible that there was only one group of builders at that time. Probably the staff of this group was flexible; the builders were independent and could be hired by anyone. Some churches were built simultaneously at the end of the 12th — beginning of the 13th century, thus we can discuss the problems of the construction process organization and the production of building materials in Novgorod at that time. Either two churches could be erected by different groups of builders or there was high level of construction process and material production organization. Probably we can combine these ideas. The process of the construction of churches lasted only for a few months; it also shows that the process itself was well-organized. The same elements of the décor, rare for Novgorod, were found in the churches built by different donators. The types and sizes of bricks, the types of lime mortar and brickwork in different monuments were the same. The production of building materials, made by craftsmen for builders, was highly developed in Novgorod at that time. An architect and a chief-master were responsible only for the building process itself. So the building group was a small flexible team of masons and carpenters which was able to transfer quickly from one construction site to another. It seems that the whole process of building was organized by a pristavnik (contractor).